2021
DOI: 10.3389/fcvm.2021.639750
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Timing of Multivessel Intervention During Index-Hospitalization for Patients With Acute Myocardial Infarction

Abstract: Background: Many patients presenting with acute myocardial infarction (AMI) were found to have a multivessel disease. Uncertainty still exists in the optimal revascularization strategy in AMI patients. The purpose of this study was to assess the outcome of immediate multivessel revascularization compared with staged multivessel percutaneous coronary intervention (PCI) in patients with AMI.Method: This was a nationwide cohort study of 186,112 patients first diagnosed with AMI, 78,699 of whom received PCI for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In their study [37], the number of patients who received BMS or plain old balloon angioplasty was approximately 18%. More recently, Liu et al [6] demonstrated that immediate M-PCI was associated with worse long-term outcomes than stage M-PCI during index admission (log-rank p < 0.001). However, their study included about 40% of STEMI patients and the deployed stents were not confined to newer-generation DES.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their study [37], the number of patients who received BMS or plain old balloon angioplasty was approximately 18%. More recently, Liu et al [6] demonstrated that immediate M-PCI was associated with worse long-term outcomes than stage M-PCI during index admission (log-rank p < 0.001). However, their study included about 40% of STEMI patients and the deployed stents were not confined to newer-generation DES.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 1, patients with cardiogenic shock were excluded in our study. Patients with NSTEMI and cardiogenic shock have worse clinical outcomes than those with STEMI and cardiogenic shock [41] and PCI of the non-IRA may aggravate hemodynamic instability and jeopardize the viable myocardium in the milieu of AMI [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obstructive lesions with smaller RVD can still affect the coronary blood flow and myocardial perfusion and result in angina, impaired quality of life, and ventricular arrhythmias 30 . Some studies have also indicated that complete revascularization in patients with CKD may attenuate the risk of sudden death or lethal arrhythmia by increasing the myocyte reserve to handle fluxes in fluid and electrolytes or transient changes in sympathetic tone 31–33 . However, PCI of very small vessels may expose these patients to acute procedural complications, increase their risk of bleeding from dual‐antiplatelet therapy, and subsequent restenosis requiring repeated angioplasty 34–36 .…”
Section: Discussionmentioning
confidence: 99%
“…30 Some studies have also indicated that complete revascularization in patients with CKD may attenuate the risk of sudden death or lethal arrhythmia by increasing the myocyte reserve to handle fluxes in fluid and electrolytes or transient changes in sympathetic tone. 31 , 32 , 33 However, PCI of very small vessels may expose these patients to acute procedural complications, increase their risk of bleeding from dual‐antiplatelet therapy, and subsequent restenosis requiring repeated angioplasty. 34 , 35 , 36 In general, treatment strategies should be individualized for this high‐risk population of patients with CKD.…”
Section: Discussionmentioning
confidence: 99%